Bionomics of a novel species of argyrotaenia (lepidoptera: tortricidae) presents in Mexican avocado orchards - Rosas-García, Ninfa M.; Villegas-Mendoza, Jesús M. (Instituto de Ecología, A.C., 2008)
A novel species of Argyrotaenia (Lepidoptera: Tortricidae) Stephens, was found in some avocado orchards in the Pacific coast from the Mexican states of Nayarit and Michoacan. Individuals obtained from the field were reared under laboratory conditions to determine their life cycle and biology. An artificial diet designed for lepidopterans, as well as a temperature of 26 ± 1ºC and a relative humidity of 65 ± 5% allowed the development of one generation per month and successful insect development. Female pupae showed an increase in weight and size through five generations, while weight and size in male pupae remained stable. The complete life cycle of this insect is around 32-36 days under laboratory conditions, and developmental stages using this diet under laboratory conditions mentioned above are as follows: egg, 5-6 days, larva, 18-20 days, pupa, 6-7 days, and adult, 15-20 days. Argyrotaenia has five larval instars in the laboratory. This study has clarified confusion surrounding this novel species of Argyrotaenia with some members of the genus Amorbia (Lepidoptera: Tortricidae), due to similarity in morphology and habits in both insects.